Análisis, diseño e implementación de un sistema de administración de contenidos e interacción de aplicaciones web que soporte un nuevo modelo conceptual orientado a la usabilidad de administradores y usuaríos - Verdezoto Dias, Nervo (2009)
Nowadays, there are Web Content Management Systems (WCMS) simple and complex. A simple WCMS has few features; they show a simple interface and a poor navigability and user interaction. While a complex WCMS has extended functionality, but with reduced navigability and its usability. Based on these arguments, this work proposes a WCMS fulfilling three basic features in a web system: functionality, nice look, and greater usability. In order to do that, we establish a conceptual model that is adequate for users and administrators of a WCMS, who don’t have the time or expertise to go through a long learning process.